Characterization of tularemia foci in the Republic of Kazakhstan from 2000 to 2020 - Izbanova, U.; Lukhnova, L.; Sadovskaya, V.; Zhumadilova, Z.; Meka-Mechenko, T.; Shevtsov, A.; Baitursyn, B.; Turebekov, N.; Tukhanova, N. (Frontiers in Epidemiology, 2024)
The wide distribution of tularemia on the territory of the Kazakhstan is associated with landscape and geographical characteristics. This is explained by a combination of natural factors: the presence of certain types of rodents -reservoirs and sources, ectoparasites -carriers of the causative agent of tularemia. The study of the current spatial and temporal characterization of tularemia in Kazakhstan from 2000 to 2020 will allow determining the epidemiological status of tularemia and improving the monitoring system in Kazakhstan.In this work we demonstrated the results of retrospective survey of natural foci of tularemia: analysis of vector, small mammal and human data. The spatial and temporal characteristics of tularemia from 2000 to 2020 on the territory of Kazakhstan were studied in comparison with historical data, including the description of tularemia outbreaks, the clinical picture, and the source of infection, transmission factors, and geographical coordinates of outbreak registration. Sampling was carried out by trapping rodents on snap traps and collecting ticks by rodent combing and by "flagging" methods. For the last 20 years, 85 human cases of tularemia have been reported. During the period from 2000 to 2020, more than 600 strains of F. tularensis were isolated from field rodents and ticks in the natural foci of tularemia. MLVA typing of F. tularensis strains isolated from natural foci of tularemia in Kazakhstan over the past 20 years.The results of retrospective monitoring indicate that currently active foci of tularemia include Aktobe, West Kazakhstan, Almaty, East Kazakhstan, Pavlodar regions. Low-activity natural foci are located on the territory of Akmola, Karaganda, North Kazakhstan, Kostanay, Atyrau, Zhambyl, Kyzylorda, regions. There are no active natural foci of tularemia in the Mangystau and Turkestan regions.The widespread occurrence of tularemia in the country is associated with landscape and geographical features that contribute to the circulation of the pathogen in the natural focus. An analysis of natural foci of tularemia showed that it is necessary to continue monitoring studies of carriers, vectors for the presence of the causative agent of the F. tularensis, in order to prevent mass cases of human disease.